Development of a Scale to Measure Consumer Skepticism Toward Advertising - Obermiller, Carl; Spangenberg, Eric R. (Journal of Consumer Psychology, 1998)
A 9‐item Likert‐type scale was developed to measure consumer skepticism toward advertising. Skepticism toward advertising, defined as the general tendency toward disbelief of advertising claims, was hypothesized to be a basic marketplace belief that varies across individuals and is related to general persuasability. A nomological network was proposed, unidimensionality and internal consistency of the scale were established, and a series of studies were conducted to establish the scale's validity and to investigate the effects of ad skepticism.